A New Class of Analytic Functions Associated with Sălăgean Operator - Muhammad Arif; Khurshid Ahmad; Jin-Lin Liu; Janusz Sokół (Journal of Function Spaces)
The main object of the present paper is to investigate a number of useful properties such as inclusion relation, distortion bounds, coefficient estimates, and subordination results for a new subclass of analytic functions which are defined here by means of a linear operator. Several known consequences of the results are also pointed out.